2014
DOI: 10.1007/s10646-014-1304-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil surface colonization by phototrophic indigenous organisms, in two contrasted soils treated by formulated maize herbicide mixtures

Abstract: Soil phototrophic microorganisms, contributors to soil health and food webs, share their particular metabolism with plants. Current agricultural practices employ mixtures of pesticides to ensure the crops yields and can potentially impair these non-target organisms. However despite this environmental reality, studies dealing the susceptibility of phototrophic microorganisms to pesticide mixtures are scarce. We designed a 3 months microcosm study to assess the ecotoxicity of realistic herbicide mixtures of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…This microcosm experiment showed that there was a strong development (4–6 μg chl a g −1 dw ) of indigenous algal and cyanobacterial crusts on soil surfaces under optimal and stable laboratory conditions. Chlorophyll a concentrations, which are a proxy for photosynthetic microbial biomass, fell in the same range as those seen in previous laboratory incubation experiments (Crouzet et al, 2013; Joly et al, 2015) and in some field studies (Tsujimura et al, 2000; Lin et al, 2013). The low values observed in the reference samples were typical for field soil samples at the end of winter (early March).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This microcosm experiment showed that there was a strong development (4–6 μg chl a g −1 dw ) of indigenous algal and cyanobacterial crusts on soil surfaces under optimal and stable laboratory conditions. Chlorophyll a concentrations, which are a proxy for photosynthetic microbial biomass, fell in the same range as those seen in previous laboratory incubation experiments (Crouzet et al, 2013; Joly et al, 2015) and in some field studies (Tsujimura et al, 2000; Lin et al, 2013). The low values observed in the reference samples were typical for field soil samples at the end of winter (early March).…”
Section: Discussionsupporting
confidence: 78%
“…Microalgae species have different pigments, and the pigment composition of a given species may vary according to its physiological state, especially if herbicides induce conditions of stress (Bérard and Pelte, 1999). That said, pigment profiling of soil or water samples remains a suitable and widely used approach for describing phytoplankton community structure (Zapata et al, 2000) and for examining how microalgal community composition responds to herbicides (Dorigo et al, 2004; Joly et al, 2015). There are few studies that have looked at the effects of phenyl-urea herbicides on soil microalgal biomass and community composition (Pipe, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were confirmed in other studies made on close soils where, however, transient effects on microbial communities structures and N‐cycling communities were observed for mesotrione mixtures with formulated S‐metolachlor and nicosulfuron, at environmental doses. No strong effects of Callisto ® used alone or in mixture at the recommended field rate were recorded in a microcosm study, on the phototrophic communities of two different soils in term of fractions and microbial diversity , which confirmed results observed in bioassays . In a study using increasing doses of mesotrione ( i.e .…”
Section: Effects Of Mesotrionesupporting
confidence: 81%
“…Moreover, an indirect stimulation of saprophytic microbial communities promoted by dead biomass from sensitive organisms (a readily available source of organic matter) may have occurred alongside a concomitant stimulation of resistant microbial population (Thirup et al 2000). A decrease in the abundance of nitrifying archaea occurred in microcosms treated by herbicide mixtures, and we also reported effects on phototrophic communities, mainly in Dual Gold Safeneur ® (alone or in mixture) treated microcosms (Joly et al 2014). These particular communities could then explain this transient increase of respiration activity without modifying the general abundance and diversity data.…”
Section: Short Term Effectsmentioning
confidence: 60%